The paradox of consumer-level open innovation collaborators in sustainable consumption transformation - Wutthiya Aekthanate Srisathan; Phaninee Naruetharadhol (Sustainable Futures)
Sustainable consumption is critical for addressing environmental challenges, yet fostering transformative behavioral shifts remains complex. This study examines the determinants of transformative sustainable consumption behavior, focusing on consumer attitudes toward sustainability, consumer collaboration, and consumer expertise, while also considering the moderating role of consumer tension. By integrating open innovation principles and exploring the paradoxical behaviors and tensions consumers experience in sustainability, the study investigates how such factors influence consumer engagement in sustainable practices and transformative consumption behavior in Thailand. Using partial least squares structural equation modeling (PLS-SEM), primary data were collected from 324 Thai consumers . The findings provide evidence of key dynamics in sustainable consumption. Consumer attitudes positively influence engagement (β = 0.153, p = 0.037), yet they negatively impact transformative sustainable consumption behavior (β = -0.148, p = 0.023), revealing an attitude-behavior gap. Consumer collaboration enhances engagement (β = 0.165, p = 0.011) but does not directly affect transformative consumption behavior (β = -0.017, p = 0.847), suggesting that collaborative efforts alone are insufficient to drive transformative change. Conversely, consumer expertise strongly predicts both engagement (β = 0.343, p < 0.001) and transformative behavior (β = 0.175, p = 0.045), highlighting the role of knowledge in fostering sustainability. Additionally, consumer tension significantly impacts transformative behavior (β = 0.247, p = 0.004), demonstrating that internal conflicts—such as financial concerns and convenience trade-offs—shape decision-making. Moderation analysis reveals that expertise buffers the negative effects of tension (β = 0.151, p = 0.005), while attitudes and collaboration are more vulnerable to psychological conflict (β = 0.100, p = 0.054; β = -0.309, p < 0.001). The findings provide practical implications for policymakers and businesses, emphasizing the need for targeted educational initiatives, policy incentives, and structured engagement models to reduce consumer tensions and enhance transformative sustainable consumption behavior.